Culture and religion in Merovingian Gaul A.D. 481 - 751 - Ḥen, Yitsḥaḳ 1963- (Cultures, beliefs and traditions, 1995)
Although often depicted as a barbaric and uncivilised society, with the full pejorative meaning of these words, Merovingian Gaul was clearly a Christian society, and a direct continuation to the Roman civilisation in terms of social standards, morals, and culture. Using insights provided by social history, archaeology, palaeography, and anthropology, this book studies the problem of christianisation in early medieval Gaul from a cultural point of view. While exploiting a huge range of primary and secondary material, the author does not confine himself to a functional analysis of various cultural and religious activities in Merovingian Gaul, but goes on to assess the consequences and implications of such activities for the people themselves, and for the subsequent developments in the Carolingian period.